Instantaneous frequency measurement with adjustable measurement range and resolution based on polarisation modulator. Issue 4 (1st February 2013) - Zhang, Hualin; Pan, Shilong
Abstract : An instantaneous frequency measurement scheme incorporating a polarisation‐modulator‐(PolM)‐based link is proposed and demonstrated. With the adjustable dispersion‐induced microwave power penalties in the PolM‐based link, the measurement range and resolution can be easily tuned. Therefore, optimised resolution for a specific measurement range can be achieved. An experiment has been performed and a frequency measurement range of 3.3–18.7 GHz with a measurement resolution of ±0.15 GHz was achieved.